“Natural Regulators”: NK Cells as Modulators of T Cell Immunity - Schuster, Iona S.; Coudert, Jerome D.; Andoniou, Christopher E.; Degli-Esposti, Mariapia A. (Frontiers in Immunology, 2016)
Natural killer (NK) cells are known as frontline responders capable of rapidly mediating a response upon encountering transformed or infected cells. Recent findings indicate that NK cells, in addition to acting as innate effectors, can also regulate adaptive immune responses. Here, we review recent studies on the immuno-regulatory function of NK cells with a specific focus on their ability to impact the generation of early, as well as long-term anti-viral T cell responses, and their role in modulating immune pathology and disease. In addition, we summarize the current knowledge of the factors governing regulatory NK cell responses and discuss origin, tissue-specificity, and open questions about the classification of regulatory NK cells as classical NK cells versus group 1 innate lymphoid cells.